The Current State of Human Resources of Healthcare: Problems and Prospects of Development - S. M. Akhtayeva; E. B. Tlessova; A. Zh. Zeinullina (Экономика: стратегия и практика, 2023)
One of the most important areas of state policy is to improve the quality of medical services. The issue of staffing becomes relevant. In recent years, there have been certain positive development trends in the dynamics of staffing of the healthcare system. But insufficient staffing of medical organizations remains a problem, which leads to a decrease in the effectiveness and effectiveness of measures aimed at improving the health of the population. The purpose of the work is to study the availability of human resources in healthcare, identify problems and develop measures for improvement. The main tasks - to study the theoretical aspects of the development of personnel policy, the analysis of personnel security, the development of recommendations for improving personnel policy. The object of the study is the healthcare personnel of the Republic of Kazakhstan. The subject of the study is the forecast of the need for medical personnel. Research methods. The following general scientific research methods are used in the work: generalization, statistical methods, comparative and regression analyses. The results. The study analyzed changes in the number of medical personnel, graduates of medical educational programs, the need for specialists was calculated using regression analysis, and the forecast of the need until 2025 was considered. The increase in the number of medical personnel needs is a significant obstacle to the provision of quality services. Conclusion. Based on the conducted research, it is necessary to increase the prestige of the doctor, develop various methods of motivating and stimulating the work of healthcare workers, implement measures to solve social problems, etc.